1997
DOI: 10.1046/j.1365-313x.1997.11051079.x
|View full text |Cite
|
Sign up to set email alerts
|

PcMYB1, a novel plant protein containing a DNA‐binding domain with one MYB repeat, interacts in vivo with a light‐regulatory promoter unit

Abstract: SummaryLight-regulatory unit 1 (LRU1) is necessary for and sufficient to mediate light-dependent activation of the chalcone synthase (CHS) minimal promoter in Petroselinum crispum. This composite promoter unit consists of at least two distinct c/s-acting elements, designated ACE ces and MRE cHs, both of which are required for light induction. The ACGT-containing element ACE cHs interacts with common plant regulatory factors (CPRFs) which belong to the basic region/leucine zipper (bZlP) class of transcription f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
95
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 146 publications
(96 citation statements)
references
References 48 publications
1
95
0
Order By: Relevance
“…However, in the case of light-regulated gene expression in plant cells, increasing lines of evidence have shown that a minimum of two different LREs in specific combinations are required to confer proper light induction (Degenhardt and Tobin, 1996;Feldbrugge et al, 1997;Puente et al, 1996). In a previous study, we have shown that only those promoters with paired LREs are able to respond to phytochrome-mediated low-fluence light pulses and are able to be activated in a tissue-specific manner (Puente et al, 1996).…”
Section: Light Regulation Of Synthetic Promoters Containing Paired Lrmentioning
confidence: 90%
See 1 more Smart Citation
“…However, in the case of light-regulated gene expression in plant cells, increasing lines of evidence have shown that a minimum of two different LREs in specific combinations are required to confer proper light induction (Degenhardt and Tobin, 1996;Feldbrugge et al, 1997;Puente et al, 1996). In a previous study, we have shown that only those promoters with paired LREs are able to respond to phytochrome-mediated low-fluence light pulses and are able to be activated in a tissue-specific manner (Puente et al, 1996).…”
Section: Light Regulation Of Synthetic Promoters Containing Paired Lrmentioning
confidence: 90%
“…However, some of the LREs are also present in promoters that are not light-regulated; and no single LRE has been found in all of the light-regulated promoters (Arguello-Astorga and Herrera-Estrella, 1996;Terzaghi and Cashmore, 1995). Recent studies have demonstrated that the combinatorial interaction of distinct LREs is required for the proper light responsiveness of promoters (Degenhardt and Tobin, 1996;Feldbrugge et al, 1997;Puente et al, 1996). These multiple LRE-containing promoters not only possess the ability to confer higher activities in light-grown plants over darkgrown plants, but also are capable of responding to phytochrome-mediated low-fluence light pulses and to developmental signals such as tissue specificity and chloroplast development.…”
Section: Introductionmentioning
confidence: 99%
“…PcMYB1 was identified by both its specific binding to MRE CHS in vitro and recognition of MRE CHS in vivo. The deduced amino acid sequence revealed that PcMYB1 contained only one MYB-like repeat (Feldbrugge et al 1997). Stracke et al (2010) reported that the bZIP transcriptional regulator ELONGATED HYPOCOTYL5 (HY5) was required for the transcriptional activation of the PFG1/MYB12 and PFG3/MYB111 genes under UV-B and visible light respectively.…”
Section: Light Responsementioning
confidence: 99%
“…An ACGT containing element (ACE) and a MYB recognition element (MRE) comprise the light regulatory unit (LRU AtCHS ), which confers responsiveness to UV-containing white light to the CHS promoter. The ACE and the MRE have been shown to be bound by basic region Leu zipper and MYB transcription factors, respectively (Armstrong et al, 1992;Feldbrü gge et al, 1997;Hartmann et al, 1998). A third cisacting element has recently been identified between the ACE and the MRE in the CHS promoter.…”
mentioning
confidence: 99%